Avaliação do comportamento de fluidos micelares na recuperação avançada de petróleo - Santos, Francisco Klebson Gomes dos (2009)
In heavy oil fields there is a great difficulty of the oil to flow from the reservoir to the well, making its production more difficult and with high cost. Most of the original volumes of oil found in the world are considered unrecoverable by the use of the current methods. The injection of micellar solutions has a direct action in the oil interfacial properties, resulting in an enhanced oil recovery. The objective of this research was the study and selection of micellar solutions with ability to decrease the interfacial interactions between fluids and reservoir formation, increasing oil production. The selected micellar solutions were obtained using commercial surfactants and surfactants synthesized in laboratory, based on the intrinsic properties of these molecules, to use in the enhanced oil recovery. Petroleum Reservoirs were simulated using sandstone plugs from Botucatu formation. Experiments with conventional and enhanced oil recovery techniques were accomplished. The obtained results showed that all micellar solutions were able to enhance oil recovery, and the micellar solution prepared with a SB anionic surfactant, at 2% KCl solution, showed the best recovery factor. It was also accomplished an economic analysis with the SB surfactant solution. With the injection of 20% porous volume of micellar solution, followed by brine injection, the increment in petroleum recovery can reach 81% recovery factor in the 3rd porous volume injected. The increment in the total cost by the addition of surfactant to the injection water represents R$ 7.50/ton of injected fluid